Myocardial lipid accumulation in patients with pressure-overloaded heart and metabolic syndrome - Raffaele Marfella; Clara Di Filippo; Michele Portoghese; Michelangela Barbieri; Franca Ferraraccio; Mario Siniscalchi; Federico Cacciapuoti; Francesco Rossi; Michele D’Amico; Giuseppe Paolisso (2009)
We evaluated the role of sterol-regulatory element binding protein (SREBP)-1c/peroxisome proliferator activated receptor-γ (PPARγ) pathway on heart lipotoxicity in patients with metabolic syndrome (MS) and aortic stenosis (AS). Echocardiographic parameters of heart function and structural alterations of LV specimens were studied in patients with (n = 56) and without (n = 61) MS undergoing aortic valve replacement. Tissues were stained with hematoxylin-eosin (H and E) and oil red O for evidence of intramyocyte lipid accumulation. The specimens were also analyzed with PCR, Western blot, and immunohistochemical analysis for SREBP-1c and PPARγ. Ejection fraction (EF) was lower in MS compared with patients without MS (P < 0.001); no difference was found in aortic orifice surface among the groups. H and E and oil red O staining of specimens from MS patients revealed several myocytes with intracellular accumulation of lipid, whereas these alterations were not detected in biopsies from patients without MS. Patients without MS have low levels and weak immunostaining of SREBP-1c and PPARγ in heart specimens. In contrast, strong immunostaining and higher levels of SREBP-1c and PPARγ were seen in biopsies from the MS patients. Moreover, we evidenced a significative correlation between both SREBP-1c and PPARγ and EF and intramyocyte lipid accumulation (P < 0.001). SREBP-1c may contribute to heart dysfunction by promoting lipid accumulation within myocytes in MS patients with AS; SREBP-1c may do it by increasing the levels of PPARγ protein. We evaluated the role of sterol-regulatory element binding protein (SREBP)-1c/peroxisome proliferator activated receptor-γ (PPARγ) pathway on heart lipotoxicity in patients with metabolic syndrome (MS) and aortic stenosis (AS). Echocardiographic parameters of heart function and structural alterations of LV specimens were studied in patients with (n = 56) and without (n = 61) MS undergoing aortic valve replacement. Tissues were stained with hematoxylin-eosin (H and E) and oil red O for evidence of intramyocyte lipid accumulation. The specimens were also analyzed with PCR, Western blot, and immunohistochemical analysis for SREBP-1c and PPARγ. Ejection fraction (EF) was lower in MS compared with patients without MS (P < 0.001); no difference was found in aortic orifice surface among the groups. H and E and oil red O staining of specimens from MS patients revealed several myocytes with intracellular accumulation of lipid, whereas these alterations were not detected in biopsies from patients without MS. Patients without MS have low levels and weak immunostaining of SREBP-1c and PPARγ in heart specimens. In contrast, strong immunostaining and higher levels of SREBP-1c and PPARγ were seen in biopsies from the MS patients. Moreover, we evidenced a significative correlation between both SREBP-1c and PPARγ and EF and intramyocyte lipid accumulation (P < 0.001). SREBP-1c may contribute to heart dysfunction by promoting lipid accumulation within myocytes in MS patients with AS; SREBP-1c may do it by increasing the levels of PPARγ protein. Metabolic syndrome (MS) is strongly associated with left ventricular (LV) hypertrophy and cardiac function derangements that lead to heart failure (HF) (1Burchfiel C.M. Skelton T.N. Andrew M.E. Garrison R.J. Arnett D.K. Jones D.W. Taylor Jr, H.A. Metabolic syndrome and echocardiographic left ventricular mass in blacks: the Atherosclerosis Risk in Communities (ARIC) Study.Circulation. 2005; 112: 819-827Crossref PubMed Scopus (77) Google Scholar). The structural basis of the progression from well-compensated hypertrophy to HF is still largely unknown in MS patients. Emerging evidence suggests that inherited and acquired cardiomyopathies, such as impaired glucose tolerance and diabetes, are associated with marked intracellular lipid accumulation in the heart (2McGavock J.M. Victor R.G. Unger R.H. Szczepaniak L.S. Adiposity of the heart, revisited.Ann. Intern. Med. 2006; 144: 517-524Crossref PubMed Scopus (311) Google Scholar, 3McGavock J.M. Lingvay I. Zib I. Tillery T. Salas N. Unger R. Levine B.D. Raskin P. Victor R.G. Szczepaniak L.S. Cardiac steatosis in diabetes mellitus: a 1H-magnetic resonance spectroscopy study.Circulation. 2007; 116: 1170-1175Crossref PubMed Scopus (481) Google Scholar). In the normal body, most triglyceride is stored in adipocytes; the amount of triglyceride stored in nonadipocyte tissues (liver, and myocardium) is minimal and very tightly regulated. However, several-fold increased cardiomyocyte triglyceride stores are observed in animal models of obesity and diabetes (4Zhou Y.T. Grayburn P. Karim A. Shimabukuro M. Higa M. Baetens D. Orci L. Unger R.H. Lipotoxic heart disease in obese rats: implications for human obesity.Proc. Natl. Acad. Sci. USA. 2000; 97: 1784-1789Crossref PubMed Scopus (1077) Google Scholar).This lipid accumulation may contribute to cardiomyocyte death by nonoxidative and oxidative (5Chiu H.C. Kovacs A. Ford D.A. Hsu F.F. Garcia R. Herrero P. A novel mouse model of lipotoxic cardiomyopathy.J. Clin. Invest. 2001; 107: 813-822Crossref PubMed Scopus (617) Google Scholar) metabolic pathways and to HF. Even in humans, myocardial lipid content was recently reported to increase with the degree of adiposity and contribute to cardiac dysfunction (6Sharma S. Adrogue J.V. Golfman L. Uray I. Lemm J. Youker K. Noon G.P. Frazier O.H. Taegtmeyer H. Intramyocardial lipid accumulation in the failing human heart resembles the lipotoxic rat heart.FASEB J. 2004; 18: 1692-1700Crossref PubMed Scopus (593) Google Scholar), suggesting that myocardial lipid content may be a biomarker and putative therapeutic target for cardiac disease in patients with MS. Genes involved in lipid metabolism are nutritionally regulated at the transcriptional level in a coordinated fashion (7Rosen E.D. Walkey C.J. Puigserver P. Spiegelman B.M. Transcriptional regulation of adipogenesis.Genes Dev. 2000; 14: 1293-1307Crossref PubMed Google Scholar). Sterol-regulatory element binding protein (SREBP)-1c is a transcription factor that controls lipogenesis and is induced during overnutrition to facilitate the conversion of glucose to fatty acids and triglycerides for the storage of excess energy (8Tontonoz P. Kim J.B. Graves R.A. Spiegelman B.M. ADD1: a novel helix-loop-helix transcription factor associated with adipocyte determination and differentiation.Mol. Cell. Biol. 1993; 13: 4753-4759Crossref PubMed Scopus (534) Google Scholar). Uncontrolled activation of nuclear SREBP-1c in the liver can cause hepatosteatosis and multiple biochemical features of the MS (9Muller-Wieland D. Kotzka J. SREBP-1: gene regulatory key to syndrome X?.Ann. N. Y. Acad. Sci. 2002; 967: 19-27Crossref PubMed Scopus (30) Google Scholar). Moreover, it has been proposed that peroxisome proliferator activated receptor-γ (PPARγ) itself is a direct target gene of SREBP-1c, providing a mechanisms by which SREBP-1c and PPARγ could cooperate to enhance lipogenesis (10Fajas L. Schoonjans K. Gelman L. Kim J.B. Najib J. Martin G. Regulation of peroxisome proliferator-activated receptor gamma expression by adipocyte differentiation and determination factor 1/sterol regulatory element binding protein 1: implications for adipocyte differentiation and metabolism.Mol. Cell. Biol. 1999; 19: 5495-5503Crossref PubMed Scopus (356) Google Scholar). Thus, it is conceivable that the SREBP-1c/PPARγ pathway deregulation might be important in the pathogenesis of lipotoxic cardiomyopathy. We hypothesized that an increase in cardiac levels of both SREBP-1c and PPARγ is involved in the adaptations of the heart to myocardial metabolic derangements and that it is potentially an important stimulus of heart adiposity and HF in MS patients. To investigate this possibility, we examined myocyte lipid accumulation and cardiac levels of SREBP-1c and PPARγ protein and mRNA in patients with and without MS who underwent surgical aortic valve replacement for aortic stenosis (AS). This is a classic model of pressure-induced concentric remodelling in humans (11Opie L.H. Commerford P.J. Gersh B.J. Pfeffer M.A. Controversies in ventricular remodelling.Lancet. 2006; 367: 356-367Abstract Full Text Full Text PDF PubMed Scopus (678) Google Scholar). We selected 282 consecutive patients who underwent aortic valve replacement for isolated AS (area≤0.715 cm2) (Table 1). The WHO criteria were used to classify patients as being with or without the MS (12WHO. Definition of metabolic syndrome in definition, diagnosis and classification of diabetes and its complications. Report of a WHO consultation. Part 1: Diagnosis and classification of diabetes mellitus. WHO/NCD/NCS/99.2. 1999. Geneve, World Health Organization-Department of Noncommunicable Disease Surveillance.Google Scholar): waist circumference (WC) >102 cm for men, >88 cm for women; blood pressure elevation >130/85 mm Hg; low HDL cholesterol <40 mg/dl in men, <50 mg/dl in women; high triglycerides >150 mg/dl; hyperglycemia, fasting glucose >100 mg/dl. The MS is considered present when at least three of the five traits are present. Among the above patients, 56 presented at least three traits of MS (4 ± 0.8) and 61 without MS (MS-traits: 1.1 ± 0.6). The remaining 165 patients were excluded because of the presence of at least one of the following conditions: diabetes, unstable angina, previous myocardial infarction, coronary stenosis >70%; renal, hepatic, rheumatic, cancerous, or other severe diseases were excluded. Insulin sensitivity was estimated from the homeostasis model assessment (HOMA) [(glucose in mmol/L × insulin in µU/ml)/22.5] (13Matthews D.R. Hosker J.P. Rudenski A.S. Naylor B.A. Treacher D.F. Turner R.C. Homeostasis model assessment: insulin resistance and beta-cell function from fasting plasma glucose and insulin concentrations in man.Diabetologia. 1985; 28: 412-419Crossref PubMed Scopus (25651) Google Scholar). All patients underwent coronary angiography before valve replacement. On the basis of ejection fraction (EF) determined by echocardiography at the time of admission, MS patients were subdivided into three groups: EF >50% (n = 18); EF 50% to 30% (n = 24); EF <30% (n = 14). The institutional Ethics Committee of the Sassari Hospital approved the study; all patients gave informed consent.TABLE 1Characteristics of the patients undergoing aortic valve replacement surgery according to the presence or absence of metabolic syndromeVariablesNo MS (n = 61)MS (n = 56)PAge, y70.3 ± 770.6 ± 6NSMale gender, n (%)44 (72)38 (69)NSBody mass index, kg/m225.6 ± 529.3 ± 4<0.001Waist circumference, cm81.1 ± 3.293.2 ± 4.1<0.001Waist circumference women, cm80.4 ± 2.887.7 ± 1.9<0.001Waist circumference men, cm82.3 ± 3.995.8 ± 5.4<0.001Risk factors Hypertension, n (%)22 (36)31 (55)<0.01 Obesity, n (%)10 (16Mihara M. Uchiyama M. Determination of malonaldehyde precursor in tissues by thiobarbituric acid test.Anal. Biochem. 1978; 86: 271-278Crossref PubMed Scopus (4299) Google Scholar)29 (52)<0.001 Hypercholesterolemia, n (%)29 (47)26 (46)NS Smokers, n (%)11 (18Barrans J.D. Allen P.D. Stamatiou D. Dzau V.J. Liew C.C. Global gene expression profiling of end-stage dilated cardiomyopathy using a human cardiovascular-based cDNA microarray.Am. J. Pathol. 2002; 160: 2035-2043Abstract Full Text Full Text PDF PubMed Scopus (157) Google Scholar)9 (16Mihara M. Uchiyama M. Determination of malonaldehyde precursor in tissues by thiobarbituric acid test.Anal. Biochem. 1978; 86: 271-278Crossref PubMed Scopus (4299) Google Scholar)NSLaboratory Glycemia, mg/dl89.2 ± 5.4113.4 ± 7.2<0.001 Triglycerides, mg/dl109.4 ± 47187.6 ± 41<0.001 HDL cholesterol, mg/dl52.3 ± 9.139.3 ± 8.9<0.01 HDL cholesterol women, mg/dl53.9 ± 6.440.4 ± 9.1<0.01 HDL cholesterol men, mg/dl51.7 ± 6.938.8 ± 8.9<0.01 Total cholesterol, mg/dl187.5 ± 26192.9 ± 24NS LDL cholesterol, mg/dl105.8 ± 19.4106.4 ± 18.3NS Insulin, µU/L7.9 ± 3.217 ± 4.8<0.001 HOMA score1.7 ± 0.44.2 ± 0.5<0.001Coronary artery disease < 70%30 (49)29 (52)NS Left main coronary stenosis, n (%)3 (5Chiu H.C. Kovacs A. Ford D.A. Hsu F.F. Garcia R. Herrero P. A novel mouse model of lipotoxic cardiomyopathy.J. Clin. Invest. 2001; 107: 813-822Crossref PubMed Scopus (617) Google Scholar)5 (9Muller-Wieland D. Kotzka J. SREBP-1: gene regulatory key to syndrome X?.Ann. N. Y. Acad. Sci. 2002; 967: 19-27Crossref PubMed Scopus (30) Google Scholar)NS Stenosis of LAD, n (%)12 (19Young M.E. McNulty P. Taegtmeyer H. Adaptation and maladaptation of the heart in diabetes: Part II: potential mechanisms.Circulation. 2002; 105: 1861-1870Crossref PubMed Scopus (399) Google Scholar)11 (20Mingrone G. Rosa G. Greco A.V. Manco M. Vega N. Hesselink M.K. Castagneto M. Schrauwen P. Vidal H. Intramyocitic lipid accumulation and SREBP-1c expression are related to insulin resistance and cardiovascular risk in morbid obesity.Atherosclerosis. 2003; 170: 155-161Abstract Full Text Full Text PDF PubMed Scopus (48) Google Scholar)NS Stenosis of LCA, n (%)15 (25Zhang Y.L. Hernandez-Ono A. Siri P. Weisberg S. Conlon D. Graham M.J. Crooke R.M. Huang L.S. Ginsberg H.N. Aberrant hepatic expression of PPARgamma2 stimulates hepatic lipogenesis in a mouse model of obesity, insulin resistance, dyslipidemia, and hepatic steatosis.J. Biol. Chem. 2006; 281: 37603-37615Abstract Full Text Full Text PDF PubMed Scopus (127) Google Scholar)13 (24Schadinger S.E. Bucher N.L. Schreiber B.M. Farmer S.R. PPARgamma regulates lipogenesis and lipid accumulation in steatotic hepatocytes.Am. J. Physiol. Endocrinol. Metab. 2005; 288: E1195-E1205Crossref PubMed Scopus (319) Google Scholar)NSActive therapy ACE inhibitors, n (%)6 (9Muller-Wieland D. Kotzka J. SREBP-1: gene regulatory key to syndrome X?.Ann. N. Y. Acad. Sci. 2002; 967: 19-27Crossref PubMed Scopus (30) Google Scholar)5 (9Muller-Wieland D. Kotzka J. SREBP-1: gene regulatory key to syndrome X?.Ann. N. Y. Acad. Sci. 2002; 967: 19-27Crossref PubMed Scopus (30) Google Scholar)NS AT2 receptor antagonists, n (%)3 (5Chiu H.C. Kovacs A. Ford D.A. Hsu F.F. Garcia R. Herrero P. A novel mouse model of lipotoxic cardiomyopathy.J. Clin. Invest. 2001; 107: 813-822Crossref PubMed Scopus (617) Google Scholar)2 (4Zhou Y.T. Grayburn P. Karim A. Shimabukuro M. Higa M. Baetens D. Orci L. Unger R.H. Lipotoxic heart disease in obese rats: implications for human obesity.Proc. Natl. Acad. Sci. USA. 2000; 97: 1784-1789Crossref PubMed Scopus (1077) Google Scholar)NS Diuretics, n (%)33 (54)29 (52)NS β-Blockers, n (%)44 (72)40 (71)NS Clonidine, n (%)12 (19Young M.E. McNulty P. Taegtmeyer H. Adaptation and maladaptation of the heart in diabetes: Part II: potential mechanisms.Circulation. 2002; 105: 1861-1870Crossref PubMed Scopus (399) Google Scholar)11 (20Mingrone G. Rosa G. Greco A.V. Manco M. Vega N. Hesselink M.K. Castagneto M. Schrauwen P. Vidal H. Intramyocitic lipid accumulation and SREBP-1c expression are related to insulin resistance and cardiovascular risk in morbid obesity.Atherosclerosis. 2003; 170: 155-161Abstract Full Text Full Text PDF PubMed Scopus (48) Google Scholar)NS Statins, n (%)27 (44)25 (45)NSEchocardiographic parameters Aortic valve area, cm20.71 ± 0.050.72 ± 0.06NS Mean aortic valve gradient, mmHg57.3 ± 458.6 ± 3NS LV mass index, g/m2118.2 ± 11.9123.7 ± 12.6NS LV septum, mm16.3 ± 315.4 ± 2.2NS LVEDD, mm49.5 ± 1046.7 ± 6NS LVESD, mm29.8 ± 531.5 ± 6NS Cardiac output, L* min−14.3 ± 1.83.9 ± 2.2NS Ejection fraction, %53.1 ± 9.841.2 ± 9.9<0.001 Myocardial performance index0.42 ± 0.090.51 ± 0.06<0.001 scFS, %118 ± 14107 ± 12<0.001 scMWS, %102 ± 1694 ± 18<0.05 esWS, dyne/cm2115 ± 24103 ± 21<0.005Heart specimen analysis Myocyte, No/mm2249 ± 32259 ± 26NS Vacuolated myocytes, %018.4 ± 6.1<0.001 Red oil staining positive myocytes, %015.1 ± 2.6<0.001 Triacylglycerol, µg/mg20.7 ± 869.1 ± 11<0.001 SREBP-1c positive myocytes, %1.5 ± 0.930.1 ± 6.3<0.001 PPARγ positive myocytes, %0.9 ± 0.318.7 ± 3.7<0.001 PPARα positive myocytes, %25.4 ± 12.326.7 ± 14.1NS PPARα protein, arbitrary units51.3 ± 18.453.6 ± 21.3NS SCD-1, arbitrary units4.3 ± 2.94.8 ± 3.1NS SERCA2a, arbitrary units88.4 ± 11.60.8 ± 9.6<0.001Data are presented as mean ± SD or n (%). MS = metabolic syndrome; HDL = high-density lipoprotein; LDL = low-density lipoprotein; HOMA = homeostasis model assessment; LDL = low-density lipoprotein. LAD = left anterior descending artery; LCA = left circumflex artery; LVEDD = left ventricular end-diastolic diamenter; LVESD = left ventricular end-systolic diameter; scFS = stress-corrected mean velocity of fiber shortening; scMWS = stress- corrected midwall fractional shortening; esWS = end-systolic wall stress; SREBP-1c = sterol regulatory element-binding protein-1c; PPAR-γ = perixome proliferator-activated receptor-γ; PPAR-α= perixome proliferator-activated receptor-α; SCD-1 = stearoyl-CoA desaturase 1; SERCA2a = sarco-endoplasmic reticulum ATPase 2a. Open table in a new tab Data are presented as mean ± SD or n (%). MS = metabolic syndrome; HDL = high-density lipoprotein; LDL = low-density lipoprotein; HOMA = homeostasis model assessment; LDL = low-density lipoprotein. LAD = left anterior descending artery; LCA = left circumflex artery; LVEDD = left ventricular end-diastolic diamenter; LVESD = left ventricular end-systolic diameter; scFS = stress-corrected mean velocity of fiber shortening; scMWS = stress- corrected midwall fractional shortening; esWS = end-systolic wall stress; SREBP-1c = sterol regulatory element-binding protein-1c; PPAR-γ = perixome proliferator-activated receptor-γ; PPAR-α= perixome proliferator-activated receptor-α; SCD-1 = stearoyl-CoA desaturase 1; SERCA2a = sarco-endoplasmic reticulum ATPase 2a. Each patient underwent an M-mode and Doppler-echocardiographic study (ATL, hdi-5000-Philips, Milan, Italy). Measurements were made according to the recommendations of the American Society of Echocardiography (14Gardin J.M. Adams D.B. Douglas P.S. Feigenbaum H. Forst D.H. Fraser A.G. Recommendations for a standardized report for adult transthoracic echocardiography: a report from the American Society of Echocardiography's Nomenclature and Standards Committee and Task Force for a Standardized Echocardiography Report.J. Am. Soc. Echocardiogr. 2002; 15: 275-290Abstract Full Text Full Text PDF PubMed Scopus (270) Google Scholar). Aortic valve annulus was measured at end-diastole in 2-dimensional parasternal long-axis. Effective aortic valve area was calculated using the continuity equation with the time-velocity integral ratio and indexed for body surface area. The LV cardiac output was calculated as the product of heart rate and stroke volume and was indexed for body surface area. The myocardial performance index (MPI), which measures both systolic and diastolic parameters of ventricular function, was calculated as previously described (15Marfella R. Siniscalchi M. Esposito K. Sellitto A. De Fanis U. Romano C. Portoghese M. Siciliano S. Nappo F. Sasso F.C. et al.Effects of stress hyperglycemia on acute myocardial infarction: role of inflammatory immune process in functional cardiac outcome.Diabetes Care. 2003; 26: 3129-3135Crossref PubMed Scopus (157) Google Scholar). The echocardiograms were interpreted blindly, without knowledge of MS presence/absence, by the operator. During open-heart surgery, myectomy samples weighing ∼10 to 30 mg were removed from the LV septum. Half of each biopsy was immediately frozen in liquid nitrogen and stored at −80°C, whereas the other half was mildly fixed in 1% paraformaldehyde, embedded in paraffin sectioned to a thickness of 5µm, and mounted on slides. Each sample was analyzed for the presence of transcripts encoding SREBP-1c, PPARγ, and adipose most-abundant gene transcript 1 (apM1). Levels of SREBP-1c and PPARγ were measured by RT-PCR amplification by using the following sense and antisense primer sequences: SREBP-1c Up 5′ GCGCAAGACAGCAGATTTATTC 3′, SREBP-1c Low: 3′ TAGATGCGGAGAAGCTGCCTA 3′; PPARγ Up 5′TCCAACTCCCTCATGGCAATTG 3′; PPARγ Low 5′ ATGAGACATCCCCACTGCAAG 3′; apM1 Up 5′GCTGGGAGCTGTTCTACTGC-3′, apM1 Low 5′ GTAAAGCGAATGGGCATGTT 3′. Appropriate regions of the hypoxanthine-phosporybosil transferase (HPRT) cDNA were amplified as control. HPRT Up: 5′ CCTGCTGGATTACATTAAAGCACTG 3′, HPRT Low: 5′ CCTCGTGGGGTCCTTTTCACCAGC 3′. (Roche Diagnostics, Italy). Each RT-PCR experiment was repeated at least three times. SREBP-1c, PPARγ, PPARα, stearoyl-CoA desaturase 1 (SCD-1), and sarco-endoplasmic reticulum ATPase (SERCA2a), proteins were determined by Western blotting analysis as previously described (16Mihara M. Uchiyama M. Determination of malonaldehyde precursor in tissues by thiobarbituric acid test.Anal. Biochem. 1978; 86: 271-278Crossref PubMed Scopus (4299) Google Scholar). The samples incubated in a buffer containing the specific antibody against SREBP-1c (sc-367; 1:100 dilution; Santa Cruz Biotechnology, Inc.), PPARγ (sc-6284; 1:100 dilution; Santa Cruz Biotechnology, Inc.), anti-PPARα (sc-9000; 1:100 dilution; Santa Cruz Biotechnology, Inc.), anti- SCD-1 (sc-14719; 1:100 dilution; Santa Cruz Biotechnology, Inc.), and anti-SERCA2a (sc-8095; 1:100 dilution; Santa Cruz Biotechnology, Inc.). The densitometric measurements were performed using the gel image system Fluor-S equipped with the analysis software Quantity One (Bio-Rad, Rome, Italy). Immunohistochemical analyses were performed as previously described (16Mihara M. Uchiyama M. Determination of malonaldehyde precursor in tissues by thiobarbituric acid test.Anal. Biochem. 1978; 86: 271-278Crossref PubMed Scopus (4299) Google Scholar). Tissues were stained with hematoxylin and eosin (H and E). The sections of heart tissue were incubated with anti-SREBP-1c (sc-367; 1:100 dilution; Santa Cruz Biotechnology, Inc.), monoclonal anti-PPARγ (sc-6284; 1:100 dilution; Santa Cruz Biotechnology, Inc.), monoclonal anti-PPARα (sc-9000 1:100 dilution; Santa Cruz Biotechnology, Inc.), and anti-myoglobin (sc-65982; 1:100 diluition; Santa Cruz Biotechnology, Inc.). Oxidative stress was determined by measuring thiobarbituric acid-reactive substances (TBARS) such as malondialdehyde (MDA) (16Mihara M. Uchiyama M. Determination of malonaldehyde precursor in tissues by thiobarbituric acid test.Anal. Biochem. 1978; 86: 271-278Crossref PubMed Scopus (4299) Google Scholar) and by the appearance of nitrotyrosine, a biomarker for nitrosative stress. Tyrosine nitration, an index of the nitrosylation of proteins by peroxynitrite and/or reactive oxygen species (ROS), was determined by immunohistochemistry as previously described (17Marfella R. Esposito K. Nappo F. Siniscalchi M. Sasso F.C. Portoghese M. Di Marino M.P. Baldi A. Cuzzocrea S. Di Filippo C. et al.Expression of angiogenic factors during acute coronary syndromes in human type 2 diabetes.Diabetes. 2004; 53: 2383-2391Crossref PubMed Scopus (98) Google Scholar). Sections were incubated overnight with anti-nitrotyrosine rabbit polyclonal antibody (1:500 in PBS, v/v). The sections were then scored for intensity of immunostaining (0 = absent, 1 = faint, 2 = moderate, and 3 = intense) for each antibody and the average value was calculated for each section. A portion of each specimen was also snap-frozen, and sections were stained with oil red O. For MDA, a portion of frozen heart tissue was ground in liquid nitrogen and homogenized. After cooling, 1:2 adduct of MDA and TBA was extracted into 4 ml of n-butanol and the absorbance was measured at 540 nm against 1,1,3,3-tetramethoxypropane used as the standard. Numbers of vacuolated myocytes, oil red O, SREBP-1c, PPARα, and PPARγ-positive cells were obtained from the entire section. Section size and number of myocytes per mm2 were determined and percentages of positive myocytes were calculated. A solution (500 µl) of 2 mM NaCl/20 mM EDTA/50 mM sodium phosphate buffer, pH 7.4, was added to myectomy samples removed from the LV septum. Then, 10 µl of homogenate was mixed with 10 µl of tert-butyl alcohol and 5 µl of Triton X-100/methyl alcohol mixture (1:1 v/v) for the extraction of lipids. Triacylglycerol was measured with a Sigma diagnostic kit. Data are presented as mean ± SD. Continuous variables were compared among the groups with one-way ANOVA for normally distributed data and the Kruskal-Wallis test for nonnormally distributed data. When differences were found among the groups, the Bonferroni correction was used to make pairwise comparisons. A p value <0.05 was considered statistically significant. Pearson r was used for bivariate correlation analysis. All calculations were performed by SPSS-12 (SPPS, Inc.). Characteristics of the study participants are reported in Table 1. MS patients did not differ from controls in terms of age, smoking, total and low-density lipoprotein cholesterol concentration, coronary artery disease, and active therapy. The MS patients had a higher prevalence of hypertension and obesity compared with patients without MS. By selection, significant differences were found for the components of the MS: body mass index (BMI), WC, fasting insulin, HOMA values, glucose, triglyceride, and HDL cholesterol levels. No differences were found in the anthropometric parameters, risks factors, laboratory analysis, and active therapy among the groups of MS patients subdivided on the basis of EF (EF >50%; EF 50% to 30%; EF <30%) (Table 2).TABLE 2Characteristics of the patients with metabolic syndrome undergoing aortic valve replacement surgery according to the ejection fraction valuesVariablesEjection Fraction >50% (n = 18)Ejection Fraction 30%-50% (n = 24)Ejection Fraction <30% (n = 14)Age, y70.6 ± 5.370.5 ± 5.270.6 ± 6.2Laboratory Glycemia, mg/dl109.1 ± 5.3112.9 ± 7.3118.2 ± 7.1* Triglycerides, mg/dl179.1 ± 45185 ± 34.8192 ± 49.7 Total cholesterol, mg/dl190.7 ± 15.4191.1 ± 22.1192.2 ± 23.6 HDL cholesterol, mg/dl41.5 ± 9.440.3 ± 8.140.2 ± 9.9 LDL cholesterol, mg/dl104.4 ± 13.3103.1 ± 14.3109.4 ± 28.4 Insulin, µU/L15.4 ± 4.416.3 ± 4.718.4 ± 5.5 HOMA score4.2 ± 0.44.2 ± 0.54.4 ± 0.5Echocardiographic parameters Aortic valve area, cm20.73 ± 0.060.71 ± 0.050.71 ± 0.06 Mean aortic valve gradient, mmHg59.1 ± 3.158.6 ± 2.958.1 ± 3.8 LV mass index, g/m2123.3 ± 8.6123.75 ± 13.6124.2 ± 15.6 LV septum, mm15.1 ± 2.215.4 ± 2.315.9 ± 2.1 Ejection fraction, %52.1 ± 1.140.7 ± 5.7*27.7 ± 1.0*+ LVEDD, mm47.7 ± 7.746.8 ± 6.145.4 ± 8.5 LVESD, mm29.2 ± 732.1 ± 533.4 ± 4 Myocardial performance index0.46 ± 0.050.51 ± 0.06*0.56 ± 0.06*+Histological analysis Myocyte, No/mm2258.7 ± 23.7258.9 ± 27.7259.5 ± 29.7 Vacuolated myocytes, %13.8 ± 4.217.6 ± 4.3*25.4 ± 4.3*† Red oil staining positive myocytes, %13.0 ± 1.415.2 ± 2.5*17.2 ± 2.8*† SREBP-1c positive myocytes, %25.6 ± 5.130.4 ± 6.0*35.3 ± 6.3*† PPARγ positive myocytes, %16.0 ± 3.318.7 ± 3.3*22.1 ± 2.8*†Data are presented as mean ± SD or n (%). *P < 0.05 compared with group with ejection fraction >50%. †P < 0.05 compared with ejection fraction between 30%-50%. Open table in a new tab Data are presented as mean ± SD or n (%). *P < 0.05 compared with group with ejection fraction >50%. †P < 0.05 compared with ejection fraction between 30%-50%. All patients showed characteristics of LV hypertrophy (Table 1). LV systolic function (EF, MPI) was impaired in MS patients: MS patients had lower EF and higher MPI (P < 0.01; Table 1). No difference in the aortic orifice surface among the groups was found (Table 1). Moreover, MS patients had EF not correlated with aortic orifice surface (R = 0.123, P = 0.154), whereas a significant correlation between aortic orifice surface and EF (R = 0.555, P < 0.001) in patients without MS was found. We did not observe adipocytes in ventricular sections. This morphological observation was supported by RT-PCR of an adipocytes-specific gene transcript (apM1) that encodes adiponectin: the apM1 transcript was almost undetectable in ventricular biopsies from all patients (Fig. 1). Moreover, the positive myoglobin staining of vacuolated cells indicates lipid accumulation in cardiomyocytes (figure, supplementary Appendix). However, H and E staining of heart specimens from MS patients revealed vacuolated cells consistent with intracellular accumulation of lipid (Fig. 2). Oil red O staining showed high lipid deposition in myocytes of MS patients (Table 1). We detected vacuolated myocytes and droplets of lipid in 53 of 56 specimens from MS patients, whereas the same myocardial alterations were not detected in biopsies from patients without MS. Moreover, triacylglycerol content was significantly higher in specimens from MS patients than in specimens of patients without MS (Table 1). Moreover, we observed that vacuolated myocytes and myocytes with lipid droplets increased with depressed EF (Fig. 2, Table 2). A positive correlation between WC and percentage of the vacuolated myocytes was observed (R = 0.315, P < 0.01). Multiple linear regression analysis revealed that WC and serum triglycerides were both independent determinants of myocardial lipid content (R = 0.324, P < 0.01; R = 0.312, P < 0.01), whereas age, BMI, and HOMA were unrelated to myocardial triglyceride content.Fig. 2Vacuolated myocytes in representative ventricular-biopsy specimens hematoxylin and eosin. The specimen from a patient without metabolic syndrome shows hypertrophied myocytes without vacuoles (×600). The specimens from a patient with metabolic syndrome shows a high number of vacuolated myocytes (×600) (A). Specimens from patients with metabolic syndrome show a progressive increase in vacuolated myocytes according to the ejection fraction (×400) (B).View Large Image Figure ViewerDownload Hi-res image Download (PPT) Figures 3 and 4 show the results of the analysis of SREBP-1c/ PPARγ proteins and mRNA levels from ventricular specimens from the groups of patients. In